The Near-Earth Asteroid Characterization and Observation (NEACO) mission - Venigalla, Chandrakanth; Baresi, Nicola; Aziz, Jonathan; Bercovici, Benjamin; Motta, Gabriel Borderes [UNESP]; Brack, Daniel; Dos Santos, Josué Cardoso [UNESP]; Dahir, Andrew; Davis, Alex B.; De Smet, Stijn; Fulton, JoAnna; Parrish, Nathan; et al. (My University, 2018)
The Near-Earth Asteroid Characterization and Observation (NEACO) mission proposes to explore the fast-rotating asteroid (469219) 2016 HO3 with a SmallSat spacecraft and perform an early scientific investigation to enable future, more in-depth missions. The NEACO spacecraft is equipped with a low-thrust, solar electric propulsion system to reach its target within two years, making use of an Earth gravity assist. Its instrument suite consists of two optical cameras, a spectrometer, an altimeter, and an explosive impactor assembly. Upon arrival at HO3, NEACO uses pulsed plasma thrusters to hover, first at a high altitude of 50 km to perform lit surface mapping and shape modeling, and later at a lower altitude of 10 km to refine these models and perform surface spectroscopy. Following the hovering phases, the spacecraft performs several flybys with decreasing periapses in order to estimate the asteroid’s mass. Finally, NEACO uses an additional flyby to release an explosive impactor that craters the asteroid surface. After spending a few weeks at a safe hovering distance, the spacecraft returns and images the crater and freshly exposed sub-surface material. This provides information on the strength of the asteroid surface. The science operations are completed within eight months, with the total mission lasting less than three years. The objectives met by the NEACO mission satisfy all science goals for the student competition of the 2017 AAS Astrodynamics Specialist Conference.